Characterization of Applied Forces and Torques During Rigid Bronchoscopy Intubation. Issue 4 (October 2020) - Barrette, Louis-Xavier; Turkseven, Melih; De, Suvranu; Majid, Adnan; Parikh, Mihir; Chee, Alex
Abstract : Background: Rigid bronchoscopy intubation poses a significant risk of complication to patients from mechanical trauma. Despite the importance of precision in forces exerted by surgeons during intubation, no prior study has analyzed the overall forces and torques involved in rigid bronchoscopy intubation, and whether existing training modalities accurately replicate them. Methods: A bronchoscope was equipped with a 6-axis load sensor to measure forces and torques applied during rigid bronchoscopy intubation. The device was applied to measure intubation forces in low-fidelity manikins and patients by interventional pulmonologists. Results: Axial and lateral forces were measured during rigid bronchoscope intubation from the mouth to the mid-trachea. The mean axial/lateral forces recorded during manikin trials were 6.93/18.06 N, whereas those recorded during patient trials were 4.57/9.43 N. Average axial and lateral force application was therefore 51.6% and 92.6% higher in manikin, respectively. Applied axial torque averaged across all human trials was 130.5 N-mm compared with 78.3 N-mm for manikin trials, 40% lower in manikin than in human. Lateral torque application during manikin intubation showed greater variation in between trials and a greater range of SDs within trials. Conclusion: This was the first application of a rigid bronchoscope measurement device designed to measure forces applied at the handle. Force and torque discrepancies between manikin training and patient applications were found, indicating a possible mismatch between the haptic feedback received by physicians during rigid training and application. This inconsistency could be resolved via novel haptic training modalities and help increase atraumatic intubations.